Characteristics of contemporary Cuban online journalism. Challenges for academic research and professional practice (Islas, 2022)
Introduction: This paper goals to characterize contemporary Cuban online journalism and to establish the professional and investigative demands that emanate from such contextual conditions.Methods: It constitutes a bibliographic-documentary research oriented to theoretical reflection on communication practices in the digital environment.Results: Among other regularities, difficulties in the processes of technological convergence as well as the reconfiguration of the public and its habits of access and use of digital media are identified.Conclutions: The urgence for journalists and academics to understand the social complexity of Cuban users, exposed to multiple sources of influence, and implement strategies to strengthen interactivity in cyberspace, is advised.
Keywords: online journalism; Cuba; interactivity; Cuban users